(untitled) (Architecture Image Studies, 2026)
This research aims to develop an interactive and validated Istima’ learning module based on the Flipped Learning approach specifically for students at State Islamic Universities in the Sumatra region. Adopting the ADDIE development model, this study focused on the three initial stages: Analysis, Design, and Development. Data were collected through literature reviews, interviews, classroom observations, and questionnaires distributed to students at UIN Suska Riau, UIN Imam Bonjol Padang, UIN Sjech M. Djamil Djambek Bukittinggi, and UIN Mahmud Yunus Batusangkar. The results of the analysis phase revealed a significant need (90%) for digital modules that support self-paced learning. Expert validation showed that the module is highly valid with an average score of 92.6%, specifically excelling in the presentation aspect (96%). Furthermore, limited trials indicated a high practicality score of 83.97%, with students reporting increased confidence and engagement in Arabic listening tasks. The integration of interactive audio-visual elements and a systematic instructional structure allows for effective pre-class independent study and active in-class discussion. This study concludes that the developed Flipped Learning module is a practical and efficient tool for modernizing Arabic language instruction in higher education.